Development of English-Based Electronic Module on Three-Variables Linear Equations System for Mathematics Education Students - Siska Candra Ningsih; Sri Wiyanah; Kintoko; Ebenezer Bonyah; Kristina Warniasih (Hipotenusa: Journal of Mathematical Society, 2025)
Many Mathematics Education students face difficulties in learning systems of linear equations in three variables, particularly when the material is delivered in English. This study aimed to develop an English-based electronic module that meets the criteria of validity, practicality, and effectiveness. Using the ADDIE development model, the product was evaluated by two validators (material expert and media expert) and implemented with 35 students enrolled in the selected topics in school mathematics course. The validation results showed that the module achieved an average validity score of 91.11% for content feasibility and 88.57% for language feasibility, indicating a ‘very valid’ category. Student responses indicated that the module was practical, with an overall practicality score of 74.17%. Effectiveness testing demonstrated that 77.14% of students met the Minimum Competency Criteria (MCC), placing the module in the effective category. These findings suggest that the English-based electronic module is feasible for use in supporting students’ conceptual understanding and strengthening language-based mathematical literacy, particularly in learning systems of linear equations in three variables.